Procedures of Translation Applied in Translating English Adverbials of Manner into Indonesian in Against All Odds - I Gusti Ayu Agung Sintha Satwika (e-Journal of Linguistics, 2023)
This study aimed to analyze the procedures involved in translatingEnglish adverbials of manner into Indonesian. The data were takenfrom a bilingual biography entitled "Against All Odds." A qualitativemethodology was employed in this study. Additionally, the data wereanalyzed using the translation procedure theory proposed by Vinay andDalbernet in Venuti (2010). The results of the data analysis arepresented using a narrative approach and descriptive sentences.According to the findings of this study’s analysis, the Englishadverbials of manner can be translated into Indonesian by applying twomethods, namely direct and oblique. Direct methods can be divided intoborrowing, calque, and literal procedures. Meanwhile, oblique methodsconsist of equivalence and transposition procedures.